The Effectiveness of Collaborative Teaching Approach to Mastering the Basic Standard of Malay Language among Students with Learning Difficulties - Asnorhisham Adam, Mohd; Rahim Hamdan, Abdul; Mohd Yusof, Sanitah; Sabiq Mohd Noor, Muhammad; Aisyah Adam, Siti; Azreen Othman, Nadiahtun (International Journal of Psychosocial Rehabilitation, 2020)
The study was conducted to examine the effectiveness of the Collaborative Teaching Approach (CTA) on the mastery of the basic standard of literacy writing in the Malay language at level one. The study was conducted as a quasi-experiment using CTA in teaching and facilitating. This study was conducted in a primary school in the Pasir Gudang district, which involved a sample of 70 students in the second year. The two teachers involved were a remedial teacher and a Malay teacher in this study. The t-test is used to test the hypothesis of the study. The findings showed that there was a significant difference in the experimental group using CTA in achieving the overall basic standard of literacy writing for Malay language students. The findings show that the use of CTA is able to increase the level of literacy mastery more effectively to the students with learning difficulties